Impact of Covid-19 on Yamuna River water quality: Possible ways to rejuvenate the riverine ecosystem in national capital of India - M, Umamah; N A Khan; N, N Sadaf; Mufti A; Farooqi I; M A Khan; Gauhar M; Kashif Ali; S Gautam; A S Khan; Renu Dhupper; Sergij Vambol (Ecological Questions, 2023)
The water quality of Yamuna River was studied for four years from 2019 until August 2022. The period witnessed the onset of COVID-19 pandemic and government-imposed complete lockdown which caused slight improvement in the water quality. Five parameters pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO) and Faecal Coliform (FC) monitored by Delhi Pollution Control Committee (DPCC) were analyzed to see the changes in water quality of Yamuna River in the Delhi stretch before the onset of COVID-19 (2019), during the COVID-19 (2020 and 2021) and after the pandemic (2022). Maximum improvement in some water quality parameters were observed only during the 1st lockdown in the year 2020 when government had imposed complete restriction on the movement of people and industries were not functioning at there maximum capacity. The water quality again declined in the year 2021 and further in the year 2022. Major cause of pollution was the untreated waste reaching the river from various drains. Therefore, it is extremely important to intersect all the major and minor drains through Sewage Treatment Plants (STPs). The floodplain of the river needs to be managed to keep the pollution in control.